Condensed Mode Cooling in Ethylene Polymerisation: Droplet Evaporation. Issue 1 (November 2013) - Alizadeh, Arash; McKenna, Timothy F.L.; Moritz, Hans‐Ulrich; Pauer, Werner
Summary A simplified model is used to explore the mechanisms for droplet vaporisation in fluidised bed reactors used for the production of polyethylene in the gas phase. Both homogeneous and heterogeneous vaporisation models are considered. It is shown that for a reasonable range of droplet sizes (less than 1 mm in diameter), droplet vaporisation will be essentially complete at bed heights on the order of 1 m.